Identificação de CNVR associadas à qualidade de carcaça e carne em bovinos da raça Nelore - Andrade, Monize Angela de (2019)
The proposal of the study was to identify structural variants in the genome, named as CNVs (copy number variations), and investigate the association of CNVRs (copy number variation regions) with carcass and meat quality traits in 658 Nellore bulls with evaluation of hot carcass weight (HCW), rib-eye area (REA), subcutaneous backfat thickness (SBT), meat tenderness (TD) after 7, 14 and 21 days of aging, intramuscular fat content (IFC) and intramuscular cholesterol content (ICC). Among those, 407 animals were genotyped with the Illumina Bovine beadchip HD® (777,962 SNPs). The PennCNV software was used to identify CNVs, which were concatenated and associated with the traits of interest by the CNVRuler program. Finally, genes overlapping total or partially the significant CNVRs (p<0.05) were identified by the BioMart package from R software using the UMD3.1 version of the bovine genome. In total, 2,119 distinct CNVs, representing 1,248 single duplications, 5 double replications, 794 single deletions and 72 double deletions, were identified. The CNVs were condensed into 475 CNVRs, covering 2.29% of the bovine genome. Of those, 59 CNVRs were significantly associated with the analyzed traits. Some genes identified in the significant CNV regions showed putative pleiotropic effect on carcass and meat quality traits, being involved in biological processes related to the immune system, cellular membrane structure, ATP binding and olfactory receptors. The identification of CNVs along the bovine genome and the association of CNVRs with carcass and meat quality traits in Nellore cattle may improve our knowledge on the biological architecture of these complex traits. In addition to enabling the development of novel selection strategies.